2019
DOI: 10.1021/acsomega.9b00054
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Water-Soluble Chlorophyll Protein (WSCP) Depends on Phytyl Conformation

Abstract: Water-soluble chlorophyll proteins (WSCP) from Brassicaceae form homotetrameric chlorophyll (Chl)–protein complexes binding one Chl per apoprotein and no carotenoids. Despite the lack of photoprotecting pigments, the complex-bound Chls displays a remarkable stability toward photodynamic damage. On the basis of a mutational study, we show that not only the presence of the phytyls is necessary for photoprotection in WSCPs, as we previously demonstrated, but also is their correct conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…An important advantage of using type II WSCPs for studying spectral tuning is the ability to rigorously modify the protein environment of the Chls by assembling them in vitro with recombinantly expressed proteins [21][22][23][24] . By implementing this strategy, Bednarczyk et al 19 demonstrated a spectral tuning mechanism based on a single-point mutation accounting for two-thirds of the spectral shifts between CaWSCP, and LvWSCP.…”
mentioning
confidence: 99%
“…An important advantage of using type II WSCPs for studying spectral tuning is the ability to rigorously modify the protein environment of the Chls by assembling them in vitro with recombinantly expressed proteins [21][22][23][24] . By implementing this strategy, Bednarczyk et al 19 demonstrated a spectral tuning mechanism based on a single-point mutation accounting for two-thirds of the spectral shifts between CaWSCP, and LvWSCP.…”
mentioning
confidence: 99%
“…4c) in Raman spectra. This interaction is expected not only to contribute to the stabilization of the complex 45 , but also to be the origin of the marked Chl b selectivity displayed by this WSCP variant 17 . This is analogous to the case of the light-harvesting 2 complex (LH2) of purple phototrophic bacterium Rhodobacter sphaeroides , in which an arginine residue has been proven to play a crucial role in binding specificity of the complex, by providing a hydrogen-bond to the C-3 1 acetyl group of the native pigment (bacteriochlorophyll a ) 46 .…”
Section: Discussionmentioning
confidence: 98%
“…Ground and Q y excited-state optimized structures for Chl-a, modified with methyl replacing phytyl, are evaluated by the CAM-B3LYP (Yanai et al, 2004 ), MN15 (Yu et al, 2016 ), ωB97xD (Chai and Head-Gordon, 2008 ), and B3LYP (Becke, 1993 ) methods using Gaussian-16 (Frisch et al, 2016 ) with the 6-31G * basis set (Hehre et al, 1972 ). Replacement of phytyl with methyl is not expected to have noticeable influences on the properties of interest herein, although its replacement with H (making a carboxylic acid) can be influential (Fiedor et al, 2003 , 2008 ; Palm et al, 2019 ). Also, the choice of basis set has a small influence (Rätsep et al, 2011 ), but as this is much less than the effect of solvent variation, it is not pursued herein.…”
Section: Methodsmentioning
confidence: 99%